Eugenia stipitata McVaugh (Myrtaceae): food resource for frugivorous flies in the state of Amapá, Brazil - Maiara Sabrine Martins Souza-Adaime; Cristiane Ramos Jesus-Barros; Maria do Socorro Miranda Sousa; Ezequiel Glória Deus; Pedro Carlos Strikis; Ricardo Adaime (Biotemas)
This work was carried out to evaluate the infestation of fruits of Eugenia stipitata McVaugh (Myrtaceae) by fruit flies in the state of Amapá, Brazil. There was 95% infestation of the green and ripe fruits. However, infestation (puparia/fruit) was higher in ripe fruits than green fruits. Four species of Tephritidae and four species of Lonchaeidae were obtained. Bactrocera carambolae (Tephritidae) predominated in ripe fruits. There was no difference in infestation by Anastrepha spp. (Tephritidae) and Neosilba spp. (Lonchaeidae) between green and ripe fruits.